2019
DOI: 10.1097/md.0000000000015787
|View full text |Cite
|
Sign up to set email alerts
|

Plate-prosthesis composite reconstruction after large segmental resection of proximal humeral tumors

Abstract: Since the standard reconstructive option after large segmental resection of proximal humeral tumors remained controversial, we designed and applied plate-prosthesis composite (PPC) for this circumstance. The purposes of the study were to: compare the functional outcome, implant survival (IS), surgical risk of PPC with those of conventional proximal humeral prosthesis (PHP); and describe the design and reconstructive procedure of PPC. Twenty patients (11 males, 9 females), who received intraarticular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In this study, the results showed that this new prosthesis did not significantly increase the operative time (151.5 min) or intraoperative hemorrhage (410 ml), indicating equivalent perioperative safety of the arthrodesis prosthesis. The mean MSTS-93 (83%) and ASES scores (79.4), as well as the ranges of flexion (71.3°) and abduction (61.3°) of this new prosthesis, were also comparable with those of our previous study and those of other studies [ 1 3 , 21 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, the results showed that this new prosthesis did not significantly increase the operative time (151.5 min) or intraoperative hemorrhage (410 ml), indicating equivalent perioperative safety of the arthrodesis prosthesis. The mean MSTS-93 (83%) and ASES scores (79.4), as well as the ranges of flexion (71.3°) and abduction (61.3°) of this new prosthesis, were also comparable with those of our previous study and those of other studies [ 1 3 , 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…Resection of the proximal humerus followed the same procedures as previously reported [ 3 , 21 ]. After removal of the tumor, we first dissected the joint capsule to expose the edge of the glenoid, after which we removed the articular cartilage and burnished the subchondral bone until spotty hemorrhage was seen.…”
Section: Methodsmentioning
confidence: 99%
“…However, for PHER, aseptic loosening is uncommon, and there are only a few studies that investigate this failure mode. 10,11,17 Further analysis revealed that periprosthetic osteolysis due to stress shielding was an important reason for aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, revision for loosened PHER remains challenging due to the rarity of this complication in PHER. Until now, few publications have specifically addressed the aseptic loosening of PHER 11,17,18 (Table 1). Wei et al described a simple revision technique that a bone cement spacer was implanted to reconstruct the bone defect after taking out the loosened PHER.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital defects, tumor resection, or traumatic injury may cause length alterations and/or segmental bone defects that may require reconstruction. In order to achieve the maximum function of the affected limb, physicians must make treatment decisions regarding the appropriate length to optimize outcomes in these populations [7][8][9]. Thus, it is important to understand the degree of normal, non-pathological bilateral asymmetry in post-industrial humans as it may influence decisions regarding operative versus nonoperative treatment.…”
Section: Introductionmentioning
confidence: 99%